Criminal Responsibility Of Women As Instrumentalities In Drug Trafficking - Sutrisno, Tri; Maryono, Maryono; Sangkhawan, Thammanoon (Journal Evidence Of Law, 2024)
This study aims to analyse the criminal responsibility of women involved in drug trafficking, especially those who are used as tools by other parties by using their names or identities as recipients of narcotics packages. The main focus of this research is to understand the factors that influence women's involvement in drug networks as well as the legal implications faced by women in the criminal justice system. The hypothesis of this research is whether women involved in drug trafficking as recipients of narcotics packages, whose names are used by other parties, can be exempted from criminal liability if there is no proven intent and power over the goods. The approach used in this research is normative law by analysing legislation and related literature. The results show that women are often trapped in narcotics networks due to exploitation and manipulation of other parties. Therefore, there is a need for legal policy reforms that are more responsive to gender issues and the protection of women's rights in drug cases. This research contributes to the development of criminal law that is more just and sensitive to social and gender factors in drug law enforcement.